Fast mobility control protocols with sink location protection in wireless sensor networks. (24th March 2015) - Chen, Xiao; Gu, Qijun; Jiang, Zhen; Wu, Jie
In this paper, we propose several novel fast converging mobility control protocols to achieve optimal deployment for streaming data flows in wireless sensor networks (WSNs). We also identify a unique sink privacy issue in mobility control protocols and propose a new privacy-preserving scheme which can be integrated into mobility control protocols to protect the sink. The simulation and performance analysis show that the proposed privacy-preserving mobility control protocols, with the sink node well-protected, can reach near-optimal results in terms of convergence speed, energy consumption and the communication cost.